Do We Know others' Visual Liking?. (December 2014) - Niimi, Ryosuke; Watanabe, Katsumi
Although personal liking varies considerably, there is a general trend of liking shared by many people (public favour). Visual liking in particular may be largely shared by people, as it is strongly influenced by relatively low-level perceptual factors. If so, it is likely that people have correct knowledge of public favour. We examined the human ability to predict public favour. In three experiments, participants rated the subjective likability of various visual objects (e.g. car, chair), and predicted the mean liking rating by other participants. Irrespective of the object's category, the correlation between individual prediction and actual mean liking of others (prediction validity) was not higher than the correlation between the predictor's own liking and the mean liking of others. Further, individual prediction correlated more with the predictor's own liking than it was with others' liking. Namely, predictions were biased towards the predictor's subjective liking (a variation of the false consensus effect). The results suggest that humans do not have (or cannot access) correct knowledge of public favour. It was suggested that increasing the number of predictors is the appropriate strategy for making a good prediction of public favour.